Factors affecting housing price in Malaysia using structural equation modeling approach - Norani Amit; Hasimah Sapiri; Zahayu Md Yusof (Penerbit Universiti Kebangsaan Malaysia, 2022)
House buyers are primarily concerned with house prices, on top of other aspects such as housing preferences, and housing financial. In Malaysia, the problem regarding housing issue is one that is regularly spoken due to sharp rise in housing prices which made that most houses are no longer affordable for most Malaysians. Thus, this study aims to identify the key factors influencing the price of houses in Malaysia. Data was collected by distributing a survey questionnaire to 245 respondents throughout the country. The data was then analyzed using the structural equation modelling (SEM) analysis via the IBM AMOS statistical software. The study instrument was evaluated using the exploratory factor analysis and confirmatory factor analysis techniques. The theoretical model was developed using the SEM technique. The findings derived are hoped to benefit policymakers, developers, urban planners, and contractors in developing strategies for materializing affordable house prices for homebuyers in Malaysia.